Modification of Microclimate for Better Growth and Develop of Summer Tomato Crop - A. M. Makeen, Asma A. M. Makeen; A. Mohamed, Habiballa; Omara, Sadig (Gezira Journal of Agricultural Science; Vol 2 No 1 (2004), 2021)
Tomato cultivars grown in Sudan are affected by the hot dry  summer climate and are highly susceptible to Tomato Yellow leaf  Curl Virus disease (TYLCV). Modification of the microclimate may decrease the effects of the hot dry conditions and improve develop- ment and yield of summer tomatoes. The present study was conducted ducted during the summer of 1998 and 1999 at the Gezira University Farm, Wad Medani, Sudan, to investigate the effects of two type of shelterbelts (Abusabeen and pigeon pea) and two irrigation intervals (3 and 7 days) on growth and development of five tomato cultivars )Omdurman, Gezira 96, Summerset 98, Strain B and Peto 86).  The results showed that the short irrigation interval was effective in  reducing the air temperature compared to long irrigation interval  Abusabeen shelter coupled with the short irrigation interval was effective in improving the microclimate, and that the pigeon pea shelter was effective in conserving soil moisture content under the two irrigation intervals. Tomato cultivars Omdurman, Gezira 96 and Summerset 98 had more vigorous growth, larger canopies and  low percentage of. flower shedding per plant within the two types of shelters under the shorter irrigation interval compared to both long irrigation interval and the control.